Prevalência de desnutrição e mensuração da qualidade de vida em pacientes oncológicos sob tratamento quimioterápico - Almeida, Liana Barbosa Macêdo (2013)
Introduction: The most common secondary diagnosis in cancer patients is malnutrition, affecting up to 80% of patients. Evidences show that malnutrition is associated with increased morbidity and mortality, poorer response to treatment, increased hospital costs and poorer quality of life. Objective: To determine the prevalence of malnutrition and measure the quality of life in cancer patients undergoing chemotherapy at Unacon-RR. Materials and methods: Quantitative, cross-sectional study, assessing the nutritional status of patients through objective methods (BMI, percentage of fat and arm muscle area) and subjective methods using the PG-SGA assessment, and the quality of life WHOQOL-Bref questionnaire. Socioeconomic and clinical data were collected to characterize the population. Results: Among men, gastrointestinal tumors were more prevalent (58.5%), while among women, breasts were the prevalent site (52%). The majority of patients were classified as eutrophic (52.2%) and only 7.5% were malnourished based by their BMI. All malnourished patients had gastrointestinal cancer, representing 24% of the cases. No woman with breast cancer presented malnutrition by this method of assessment. The assessment by PG-SGA, showed that 70.1% of patients were malnourished, represented by 88% of patients with gastrointestinal cancer, and 35.3% of women with breast cancer. The quality of life assessment reveled that the most affected domain was the physical, in all groups of patients. The well-nourished patients had significantly higher quality of life than malnourished patients. Conclusion: There was compromised nutritional status in patients, especially when evaluated by PG-SGA, which turned out as a more sensitive method, compared to the other objective methods. The quality of life of patients was compromised, especially in the physical domain and there was a strong correlation with nutritional status.